Analysis economic resilience of tourism worker families in the post COVID-19 pandemic recovery in Badung Regency, Bali province - Widiana, I Nyoman Wahyu; Saskara, Ida Ayu Nyoman; Dewi, Made Heny Urmila; Suasih, Ni Nyoman Reni (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic significantly impacted the tourism sector, particularly in regions heavily dependent on tourism, such as Badung Regency in Bali Province. During the post-pandemic recovery phase, understanding the economic resilience of families involved in tourism is crucial for promoting sustainable development. This study investigates family economic resilience in Badung Regency, focusing on gender and location as key variables. Data were collected from 204 respondents through quota sampling, utilizing a logit model for analysis. Control variables included homeownership, family income, financing for children’s education, savings, health insurance, household expenditures, family size, education levels of respondents and their partners, and debt ownership. The results reveal that female tourism workers exhibit stronger family economic resilience compared to their male counterparts. Additionally, rural tourism workers demonstrate greater resilience than those in urban areas. These findings underscore the vital role of women and rural tourism communities in economic recovery efforts. The study recommends implementing gender-inclusive and location-sensitive recovery strategies, such as improving access to financial capital, capacity-building programs, and expanding market opportunities for women and rural tourism stakeholders. Strengthening these areas will enhance long-term family economic resilience and support sustainable post-pandemic recovery in regions dependent on tourism.